Exploration of Co-Creation Strategy: On the “Collaboration for Innovation” Program in the Digital Era - Ida Ayu Parwati; Ida Ayu Oka Martini (Jurnal Mamangan, 2024)
This research seeks to understand the exploration of co-creation strategies in the collaborative strategy program for innovation in the digital era at Bank OCBC through a qualitative descriptive approach. Study data was collected through documentation, observation, and conducting in-depth interviews directly with 4 informants. The data was then analyzed using a triangulation approach, both sources and techniques, which were guided by the theory of Miles et al. The findings indicate that marketing strategies in the current digital era see collaboration between companies and customers through co-creation. At Bank OCBC, it is implemented well by paying attention to dialogue, access, risk assessment and transparency (DART) in the current era of digital disruption, the co-creation process used by Bank OCBC can be shortened by using platforms such as websites and social media so that it takes advantage of this platform by exchanging ideas with customers to see what they want about current banking products or asking for reviews regarding products that OCBC Bank already has and customer satisfaction in using the products they have so that it has an impact on sustainability. This study is able to make a positive contribution to marketing literature in product marketing and practically for banks in maintaining the business sustainability of financial institutions in Indonesia.